Skrining Fitokimia Berbagai Fraksi Ekstrak Buah Lakum (Cayratia trifolia L.) - Elvi Rusmiyanto, Catur Wulandari, Diah Wulandari Rousdy, (Jurnal Protobiont, 2018)
Lakum fruit (Cayratia trifolia L.) is one of the plant which is predicted to have antioxidant activity. The aim of present study is to investigate the presence of phytoconstituents in the different fractions like ethyl acetate, methanol and n-hexane of lakum fruit extract. The fruit was extracted using methanol solvent. The result of fractionations showed that the ethyl acetate fraction have yield of 19,7%, while the methanol fraction have yield of 16,8% and the n-hexane fraction have yield of 2,26%. The ethyl acetate and methanol fractions were showing alkaloids and phenolic compounds, while n-hexane fraction only show alkaloids.